2006
DOI: 10.1097/00124645-200607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Calculation Skills of Practicing Nurses and Senior Nursing Students

Abstract: Medication administration is an essential nursing competency as calculation difficulties can lead to serious medication errors. Nurses involved in staff education need to be aware of methods to assess for computation difficulty and develop strategies for nurses to improve their computation abilities. The purposes of this quasi-experimental pilot study were to assess the medication calculation skills of nurses and nursing students and to determine the effectiveness of teaching strategies aimed at improving thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
1
16
0
4
Order By: Relevance
“…Three studies in the United States of America on medication calculation ability have significantly better pretest results than the current study, but similar post-test results 7,8,9 . Comparatively, the Tanzanian students may have lacked knowledge in the pretest, they were motivated and able to learn effectively.…”
Section: Discussionsupporting
confidence: 63%
“…Three studies in the United States of America on medication calculation ability have significantly better pretest results than the current study, but similar post-test results 7,8,9 . Comparatively, the Tanzanian students may have lacked knowledge in the pretest, they were motivated and able to learn effectively.…”
Section: Discussionsupporting
confidence: 63%
“…18 Several studies and reports demonstrate the need to make mathematical calculations a priority focus area. 19,20 More than 1 in 6 medication errors involve a calculation error. [21][22][23] A simulated study in a pediatric stabilization unit in England found that 14.2% of 150 orders were converted from milligrams to milliliters incorrectly, with a maximum dose deviation of 400%.…”
Section: Principles Of Safe Medication Administrationmentioning
confidence: 99%
“…These have ranged from traditional pedagogic efforts [5] -more teaching -to the development of interactive learning environments [6]. Although educational programmes do much to address arithmetical shortcomings, they provide little insight into whether the traditional textual layout of information used during calculations is best suited to the task that nurses face.…”
Section: Introductionmentioning
confidence: 99%